(untitled) - Ramage, John D (Boston, 2012)
This book is basically a high school book assigned to college students. It gets you all the basic rhetorical strategies you'll need, but the example arguments they give you are far from mature academic writing.
Keywords: English language,Persuasion (Rhetoric),Report writing,Kỹ năng viết báo cáo; Rhetoric